Cationic, water-soluble, fluorene-containing poly(arylene ethynylene)s: Effects of water solubility on aggregation, photoluminescence efficiency, and amplified fluorescence quenching in aqueous solutions - Huang, Y.-Q. (2014)
10.1002/pola.21628